Güncel Ortodonti Çalışmaları III (Bahar) - Erdem, Merve Ece; Irgın, Celal; Evrenol, Berna; Sadry, Sanaz; Bilici Geçer, Rumeysa; Düzgün, Cansu; Atabay, Fatih; Ay Ünüvar, Yazgı; Ünlüoğlu, Özge; Bilginer, Pervin (Academician Publishing Book DOI Portal, 2024)
-